Answer:
In step-by-step-explanation
Explanation:
2) ( x + 1 ) * ( x - 7 ) = x² - 7x + x - 7 ⇒ x² - 6x - 7
In x² - 6x - 7 a = 1 b = -6 c = -7
3) ( x + 9 ) * ( x + 2 ) = x² + 2x + 9x + 18 ⇒ x² + 11x + 18
In x² + 11x + 18 a = 1 b = 11 c = 18
4) ( x - 5 ) * ( x - 3 ) = x² - 3x - 5x + 15 ⇒ x² - 8x + 15
In x² - 8x + 15 a = 1 b = -8 c = 15
5) ( x + 15 ) * 2 * ( x - 1 ) ⇒ ( x + 15 ) * ( 2x - 2 ) ⇒ 2x² -2x + 30x - 30
2x² + 28x - 30 a = 2 ² b = 28 c = 30
6) ( x - 5 ) * ( 4x - 3 ) ⇒ 4x² - 3x - 20x + 15
In 4x² - 3x - 20x + 15 ⇒ a = 4 b = -20 c = 15